Hak Dan Kewajiban Suami Istri Dalam Pernikahan Jarak Jauh (LDR) Perspektif Fiqih Keluarga Islam - Annita Putri Aisyah; Tri Julita (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study discusses the protection of husbands’ and wives’ rights in long-distance marriages, which increasingly occur due to work, education, and other particular circumstances. Long-distance marriages create various challenges in fulfilling the rights and obligations of both spouses, physically and emotionally, thereby requiring an understanding of legal and moral protection for both parties. This research aims to analyze the forms of protection for husbands’ and wives’ rights in long-distance marriages from the perspective of Islamic family law. The method used in this study is normative legal research with a qualitative descriptive approach through the examination of the Qur’an, hadiths, Islamic legal literature, and related regulations. The results show that the protection of spouses’ rights in long-distance marriages can be realized through good communication, fulfillment of financial support, maintaining loyalty, and carrying out mutual responsibilities based on the principles of justice and deliberation in Islam. Therefore, long-distance marriages can still achieve a harmonious family life when both parties properly fulfill their respective rights and obligations.